Suburban Self-suffi cient Living: an Implementation of the Philosophy of Sufficiency Economy - Hengrasmee, Sirimas (Nakhara : Journal of Environmental Design and Planning, 2012)
Sufficiency signals a combination of having enough and being satisfi ed. In Thailand, the idea of suffi ciency has been reintroduced as the philosophy of Suffi ciency Economy. Self-reliance and selfsufficiency are playing a big part of its implementation. This paper suggests a hypothetical adaptation of suburban lifestyles under such philosophy, where the immediate environment of the house is considered the main source for exploitation of food, water, and energy. It illustrates the possibility of being more self-reliant at a household level. The link between outcomes and the reduction of environmental impacts through simple Ecological Footprint estimation affi rms that practice of self-suffi ciency and sustainability are compatible.